If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -1m) = 7m + 17 + -2m (4 * 3 + -1m * 3) = 7m + 17 + -2m (12 + -3m) = 7m + 17 + -2m Reorder the terms: 12 + -3m = 17 + 7m + -2m Combine like terms: 7m + -2m = 5m 12 + -3m = 17 + 5m Solving 12 + -3m = 17 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 12 + -3m + -5m = 17 + 5m + -5m Combine like terms: -3m + -5m = -8m 12 + -8m = 17 + 5m + -5m Combine like terms: 5m + -5m = 0 12 + -8m = 17 + 0 12 + -8m = 17 Add '-12' to each side of the equation. 12 + -12 + -8m = 17 + -12 Combine like terms: 12 + -12 = 0 0 + -8m = 17 + -12 -8m = 17 + -12 Combine like terms: 17 + -12 = 5 -8m = 5 Divide each side by '-8'. m = -0.625 Simplifying m = -0.625
| -3=(-1/5)-10 | | 11x-(3x-7)=23 | | 7x+5x-5=3(4x+1) | | 7x-14=3x+18 | | 2x-7=6-6x-2x | | 32/x=x/2 | | 60x-30=15(4x-2) | | (63+9)/3 | | 490=7n | | 3/49=26/7x | | 15z^2+14z-8=0 | | -2y^2+1y+10=0 | | 6(y)-13=-13 | | x^2+8x-12=x^2 | | p-1=5p-8+3p | | 47x+94=47x+81 | | 8.3=4(k)-2.5 | | x^2+8-12=x^2 | | 3+3(2x-1)=14+4x | | 4x-16/3x-12 | | 16m+15m^2-15= | | 3(p)-14=9 | | 7(t)-20=33 | | -14=10-2x | | 8z+12z=5z-21 | | 3x+x+4=8x-4x+4 | | 5(w+4z)-5(w+3)=8 | | 4+6r-r=-5+8r | | x+9=-17 | | 10x+x=196 | | (1/4)(p)+6=8 | | 6x+39x-7=9(5x+6) |